Development and evaluation of an instrument to examine young children’s knowledge of the biological concept of structure and function - Flores, Pamela; Boone, William J.; Neuhaus, Birgit J. (Frontiers in Education, 2025)
One important line of inquiry pursued by researchers has focused on the development of instruments to assess students’ knowledge of different scientific concepts. In the field of life science, the vast majority of instruments discussed in the literature assess high school and primary school students. Very few assessment tools exist that focus on younger children. Given that the development of conceptual understanding is a central aim of early science education, there is a need for instruments that measure preschool children’s knowledge in an age-appropriate manner. In this paper, we present an instrument that measures young children’s knowledge of the biological concept of “structure and function.” We made use of Rasch psychometric techniques to assess the measuring functioning of the instrument, including the analysis of dimensionality, item and person reliability, step ordering, and the range of item difficulty in relation to the range of person ability. Our analysis revealed that the instrument exhibited strong psychometric properties. The results indicate that children’s conceptual knowledge can be characterized through two different cognitive activities: (1) recognizing the relation between biological structures and their respective functions, and (2) explaining these relations, and that these cognitive activities are related to each other. Further, the results reveal a great variance in children’s abilities and contribute to the theory of previous studies regarding the link between children’s previous experiences and their conceptual understanding. Overall, these results indicate that our instrument provides an appropriate tool to measure young children’s conceptual understanding of structure and function. Implications for young children’s science education are discussed.